The Casework Approach in Handling Children Experiencing Psychosocial Trauma - Mahdy Afif Tasdid (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines the casework approach in handling children experiencing psychosocial trauma. The topic is significant because psychosocial trauma affects not only children's psychological well-being but also their behavior, social relationships, educational participation, sense of security, and overall social functioning. Children exposed to physical, emotional, or sexual abuse, neglect, bullying, family conflict, or the loss of caregivers require comprehensive and child-centered interventions. This study aims to explain the characteristics of psychosocial trauma in children, analyze the stages of the casework approach, and describe the roles of social workers in facilitating children's recovery. A qualitative descriptive design employing a literature review was adopted. Data were obtained from scholarly books, peer-reviewed journal articles, official reports, and policy documents related to social work, child protection, psychosocial trauma, and clinical social work interventions. The findings indicate that the casework approach provides a systematic framework encompassing engagement, assessment, intervention planning, implementation, evaluation, termination, and follow-up. Social workers perform multiple professional roles, including assessor, counselor, advocate, broker, mediator, case manager, and service coordinator. Effective implementation of casework requires trauma-informed, ethical, child-friendly, and multidisciplinary practices to promote sustainable psychosocial recovery and strengthen children's resilience.